Special issue on 'reconceiving civil society and transitional justice: lessons from Asia and the Pacific'. Issue 2 (4th May 2019) - Wallis, Joanne; Kent, Lia
ABSTRACT: This article, and the special issue it introduces, joins an emerging conversation about the role of civil society in transitional justice (TJ). Although civil society organisations play an integral role in the pursuit of TJ in conflict-affected societies, the literature lacks a comprehensive conceptualisation of the diversity and complexity of these roles. Building on an interdisciplinary workshop at the Australian National University in September 2016, the contributions to this special issue explore the forms of civil society that are enabled and disabled by TJ processes and the forms of TJ activity that are enabled and disabled by different kinds of civil society actors.